If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -8(8 + 7n) = -5 + 2n 1 + (8 * -8 + 7n * -8) = -5 + 2n 1 + (-64 + -56n) = -5 + 2n Combine like terms: 1 + -64 = -63 -63 + -56n = -5 + 2n Solving -63 + -56n = -5 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -63 + -56n + -2n = -5 + 2n + -2n Combine like terms: -56n + -2n = -58n -63 + -58n = -5 + 2n + -2n Combine like terms: 2n + -2n = 0 -63 + -58n = -5 + 0 -63 + -58n = -5 Add '63' to each side of the equation. -63 + 63 + -58n = -5 + 63 Combine like terms: -63 + 63 = 0 0 + -58n = -5 + 63 -58n = -5 + 63 Combine like terms: -5 + 63 = 58 -58n = 58 Divide each side by '-58'. n = -1 Simplifying n = -1
| 8+-5= | | x+2.7=10.3 | | 36-4=6b+8 | | 3(4x+5)=-41+32 | | 23+-31= | | -7p+5(2p+1)=5+5p | | 7/3t/4=t/8 | | 6x-11-3x=5x-8 | | 2x-5+4x=3x+4 | | 1374879-657657635+65357f=k | | -4x+9=8 | | 16x-2=5+15x | | c=4az | | -15+4g=-335 | | 2x-6=38x | | -2x-5y-6x+4y= | | c=45+0.20(200) | | -15+-11= | | 4m+8(m-5)=-23-5m | | 9=5(8-k) | | 15+15x+16x+7=180 | | 4y+2(y-2)=8y-4(y-10) | | 5.12x-3.4=11.447 | | 3m+15=2m+10 | | 800-5p=q | | 2(3h-6)=5-(h-4)+7h | | (x+1)*(2x+6)=(-5x+7)*(x+1) | | -10s=-50 | | c=45+0.20(150) | | 8+2+600=610 | | -2(-5-32)=7z | | -6+8-8= |